ANALISIS KEBUTUHAN KETERAMPILAN MEMBACA KRITIS SISWA KELAS VII - wulandari, catur; Suhardi, Suhardi; Syamsi, Kastam (UNIB Press, 2022)
This study aims to identify the needs of teachers and students on critical reading skills. This research uses descriptive quantitative research. Data collection tools are questionnaires and interviews. The subjects of this study were 23 grade VII students and 21 Indonesian language teachers in grade VII SMP who were members of the Subject Teacher Consultative Forum (MGMP), Sleman Regency, Yogyakarta. The results showed that female and male students had the same interest in reading activities, most of the students preferred to learn by discussion. Before reading the text, most of the students tried to guess the reason the author wrote the text, guessed the contents of the text from titles, and make questions to guide. From the teacher's perspective, it was found that the teacher felt that learning to read critically was a difficult task, the teacher needed a reading learning model using discussion. From the interviews, it turned out that the teacher had not taught critical reading skills in class. Critical reading skills are very important and needed by students today. Therefore, the critical reading learning model with discussion is very much needed by teachers and students.